CONSCIÊNCIA POLÍTICA E PARTICIPAÇÃO: UMA ANÁLISE NO COOPERATIVISMO DE CRÉDITO RURAL SOLIDÁRIO - Santos, Suellen Nascimento dos (2021)
Solidary economy credit cooperatives are classified as financial institutions that follow the rules and procedures of the Central Bank of Brazil (Bacen), but are part of the cooperative movement. These cooperative organizations face difficulties in operat